Risk factors for infective endocarditis in children with congenital heart diseases - A nationwide population-based case control study. (1st December 2017) - Sun, Li-Chuan; Lai, Chih-Cheng; Wang, Cheng-Yi; Wang, Ya-Hui; Wang, Jen-Yu; Hsu, Yo-Ling; Hu, Yin-Lan; Wu, En-Ting; Lin, Ming-Tai; Sy, Leticia B.; Chen, Likwang
Abstract: Background: Infective endocarditis (IE) is uncommon in childhood. Its associated epidemiological characteristics in patients with congenital heart disease (CHD) remain unclear. Methods: The study population included children born in Taiwan during the years 1997 to 2005 who were diagnosed as having CHD before 3 years of age. All children were followed up until the end year of 2010, the diagnosis of infective endocarditis, or death. The demographic characteristics of patients with and without IE, the invasive procedures performed during 6 months before the index date, the prophylactic antibiotics related to dental procedures, and in-hospital mortality were collected. Results: Information of 24, 729 children with CHD were retrieved for our analysis and 237 patients with newly diagnosed IE were identified. The incidence rate of IE in all CHD lesions was 11.13 per 10, 000 person-years. Taking ASD for reference, the following CHD lesions were at risk for IE: cyanotic CHD (adjusted OR, 9.58; 95% confidence interval, 5.38–17.05), endocardial cushion defect (ECD) (8.01; 2.73–23.50), Left-sided lesions (4.36; 1.90–10.01) and VSD (2.93; 1.64–5.23). Patients who underwent procedures have a higher risk of acquiring IE which include central venous catheter (CVC) insertion (3.17; 2.36–4.27), cardiac catheterization (3.74; 2.67–5.22), open-heart surgery (2.47; 1.61–3.77), valve surgery (3.20; 1.70–6.02), and shunt surgery (7.43; 2.36–23.41). However, dental procedures did not increase the risk of IE, irrespective of antibiotic usage. Conclusions: The risk of IE varies markedly among CHD lesions in our study. Invasive heart procedures but not dental procedures, are more significantly associated with IE among children with CHD.